Yield performance of high-yield rice varieties in swamp lands of the West Kalimantan border area - Alwi Muhammad; Hairani Anna; Napisah Khairatun; Agustina Rusmila; Fadhilah Nur (BIO Web of Conferences)
The planting season has a significant impact on the rice yield in tidal type C. Farmers in Matang Danau Village, Paloh Sub-District, Sambas District, West Kalimantan Province, currently cultivate rice once a year during the rainy season (RS), using the Cilosari, which has a low yield of 2.35 t ha-1. To increase the cropping index (CI), water pumping can be utilized during the dry season (DS), along with the use of high-yield varieties. This research aimed to evaluate the yield performance of various high-yield rice varieties in the swamp lands of the West Kalimantan border area. Conducted during the DS (March to July 2018) and RS (October 2018 to February 2019), the research used a randomized complete block design with three replications. The varieties tested included Inpara 1, 2, 3, 4, 6, 8, 9, Inpari 32, and control varieties Margasari and Cilosari. Results indicated significant yield differences among the varieties under swamp conditions, with Inpara 1 achieving the highest yield of 6.6 t ha-1, while other varieties ranged from 3.98 to 5.90 t ha-1. Inpara 1 showed the most notable yield improvement compared to Margasari and Cilosari. Additionally, yields during the RS were 89.4% higher than those during the DS.